Perspektif Hadis Tentang Sifat Ketawa Allah: Hadith Perspective on the Nature of Allah's Laughter - Muhammad Istiqamah (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
The hadiths which mention the nature of Allah Swt.'s "laughter" are part of a complex discussion in Islamic theological discourse, especially in the study of Asmā' wa Ṣifāt. This characteristic is included in the category of khabariyyah (based on news) characteristics which outwardly resemble the actions of creatures. This research aims to examine in depth the hadiths that mention Allah's laughter, the validity of their sanad, the meaning they contain, as well as the approach of the scholars in interpreting them. Using a literature study method and a descriptive-analytical approach, this paper shows the diversity of approaches between the Salaf and Khalaf groups in understanding this nature. On the one hand, a literal understanding is accepted within the limits of tanzih (purification from likeness), and on the other hand, there is a more rationalistic approach to takwil. This study emphasizes the importance of the principle of bilā kayf and caution in understanding the nature of Allah in order to avoid deviations from the faith.